Up Regulation of cystathione γ lyase and Hydrogen Sulphide in the Myocardium Inhibits the Progression of Isoproterenol–Caffeine Induced Left Ventricular Hypertrophy in Wistar Kyoto Rats - Ahmad, A.; Sattar, M.A.; Rathore, H.A.; Abdulla, M.H.; Khan, S.A.; Azam, M.; Abdullah, N.A.; Johns, E.J. (Public Library of Science, 2016)
Hydrogen sulphide (H2S) is an emerging molecule in many cardiovascular complications but its role in left ventricular hypertrophy (LVH) is unknown. The present study explored the effect of exogenous H2S administration in the regression of LVH by modulating oxidative stress, arterial stiffness and expression of cystathione γ lyase (CSE) in the myocardium. Animals were divided into four groups: Control, LVH, Control-H2S and LVH-H2S. LVH was induced by administering isoprenaline (5mg/kg, every 72 hours, S/C) and caffeine in drinking water (62mg/L) for 2 weeks. Intraperitoneal NaHS, 56μM/kg/day for 5 weeks, was given as an H2S donor. Myocardial expression of Cystathione γ lyase (CSE) mRNA was quantified using real time polymerase chain reaction (qPCR).There was a 3 fold reduction in the expression of myocardial CSE mRNA in LVH but it was up regulated by 7 and 4 fold in the Control-H2S and LVH-H2S myocardium, respectively. Systolic blood pressure, mean arterial pressure, pulse wave velocity were reduced (all P<0.05) in LVH-H2S when compared to the LVH group. Heart, LV weight, myocardial thickness were reduced while LV internal diameter was increased (all P<0.05) in the LVH-H2S when compared to the LVH group. Exogenous administration of H2S in LVH increased superoxide dismutase, glutathione and total antioxidant capacity but significantly reduced (all P<0.05) plasma malanodialdehyde in the LVH-H2S compared to the LVH group. The renal cortical blood perfusion increased by 40% in LVH-H2S as compared to the LVH group. Exogenous administration of H2S suppressed the progression of LVH which was associated with an up regulation of myocardial CSE mRNA/H2S and a reduction in pulse wave velocity with a blunting of systemic hemodynamic. This CSE/H2S pathway exhibits an antihypertrophic role by antagonizing the hypertrophic actions of angiotensin II(Ang II) and noradrenaline (NA) but attenuates oxidative stress and improves pulse wave velocity which helps to suppress LVH. Exogenous administration of H2S augmented the reduced renal cortical blood perfusion in the LVH state.